Effects of soluble β-amyloid on the release of neurotransmitters from rat brain synaptosomes - Olivero, Guendalina; Grilli, Massimo; Chen, Jiayang; Preda, Stefania; Mura, Elisa; Govoni, Stefano; Marchi, Mario (Frontiers in Aging Neuroscience, 2014)
Contradictory results have been reported on the interaction of beta-amyloid (Aβ) with cholinergic receptors. The present paper investigates the modulatory effect of Aβ1-40 on the neurotransmitter release evoked by nicotinic (nAChRs) and muscarinic (mAChRs) receptors. Aβ1-40 inhibits both nicotinic and muscarinic-evoked [3H]DA overflow from rat nerve endings. Added to perfusion medium, Aβ1-40 is able to enter into synaptosomes; it exerts its inhibitory effect at extracellular sites when release is stimulated by nAChRs and intracellularly when release is evoked by mAChRs. Moreover, our data show that Aβ1-40 acts as non competitive antagonist of heteromeric α4β2* but not of α3β4* nAChRs which modulate [3H]NA overflow. Positive allosteric modulators of nAChRs counteract its inhibitory effect. It might be that compounds of this type could be useful to prevent, slow down the appearance or reverse the cognitive decline typical of the normal processes of brain aging.